Tabebuia avellanedae naphthoquinones: activity against methicillin-resistant staphylococcal strains, cytotoxic activity and in vivo dermal irritability analysis - Giambiagi-deMarval Marcia; Pinto Antonio; Damaso Clarissa; Jesus Desyreé; Leal Ivana; Machado Thelma; Pereira Eliezer; Kuster Ricardo; dos Santos Kátia (BMC, 2006)
Abstract Background Methicillin-resistant Staphylococcus aureus (MRSA) and coagulase-negative staphylococcus infections are a worldwide concern. Currently, these isolates have also shown resistance to vancomycin, the last therapy used in these cases. It has been observed that quinones and other related compounds exhibit antibacterial activity. This study evaluated the antibacterial activity, toxicity and in vivo dermal irritability of lapachol extracted from Tabebuia avellanedae and derivatives against methicillin-resistant staphylococcal isolates. In addition, its mechanism of action was also analyzed. Methods The compounds β-lapachone, 3-hydroxy β N lapachone and α-lapachone were tested to determine the MIC values against methicillin-resistant S. aureus, S. epidermidis and S. haemolyticus strains, being the two last ones hetero-resistant to vancomycin. Experiments of protein synthesis analysis to investigate the naphthoquinones action were assessed. In vitro toxicity to eukaryotic BSC-40 African Green Monkey Kidney cell cultures and in vivo primary dermal irritability in healthy rabbits were also performed. Results The compounds tested showed antibacterial activity (MICs of 8, 4/8 and 64/128 μg/mL to β-lapachone, 3-hydroxy β N lapachone and α-lapachone, respectively), but no bactericidal activity was observed (MBC > 512 μg/mL for all compounds). Although it has been observed toxic effect in eukaryotic cells, the compounds were shown to be atoxic when applied as topic preparations in healthy rabbits. No inhibition of proteins synthesis was observed. Conclusion Our results suggest that quinones could be used in topic preparations against wound infections caused by staphylococci, after major investigation of the pharmacological properties of the compounds. Studies about the use of these compounds on tumoral cells could be carried on, due to their effect in eukaryotic cells metabolism.